Application of Blockchain Technology in Online Education - Sun, Han; Wang, Xiaoyue; Wang, Xinge (International journal of emerging technologies in learning, 2018)
Blockchain is a data structure of data blocks arranged in chronological order. It is featured by decentralization, trustworthiness, data sharing, security, etc. It has been widely used in digital currency, smart contract, credit encryption and other fields. With the development of the Internet technology, online education, a novel education mode, has been greatly popularized. However, this education mode still faces many problems in course credibility, credit and certificate certification, stu-dent privacy, and course sharing. Through literature review and case analysis, this paper discusses the basic technical principles and application features of blockchain technology, and proposes a solution to the problems of online educa-tion based on blockchain technology. The blockchain technology can store learn-ing records in a trusted, distributed manner, provide credible digital certificates, realize learning resource sharing with smart contract, and protect intellectual property through data encryption. The research shows that the integration of blockchain technology is a promising trend in the development of online educa-tion.